Soldiers on the Digs. Archaeological Excavations in Switzerland Involving the Deuxieme Division des Chasseurs - Piotr Włodarczak; Urs Leuzinger (Archaeologia Polona, 2023)
During the Second World War, Polish soldiers of the 2nd Rifle Division (Deuxieme Division des Chasseurs) were interned in Switzerland. Some of them were briefly employed on archaeological excavations in the cantons of Aargau, Lucerne, Solothurn, and Thurgau. In this last location, Karl Keller-Tarnuzzer organised the most productive cooperation with the Poles, investigating the pile-dwelling settlements of Pfyn-Breitenloo and Arbon-Bleiche 2 in 1944 and 1945, respectively. Earlier, Polish soldiers had been employed in the investigation of Roman villas at Aeschi (Solothurn) and Bellikon (Aargau), and the Neolithic pile-dwelling settlement of Burgäschisee-Ost (Solothurn), among other sites. The work involving the Poles was usually carried out efficiently, to the satisfaction of both sides. It has earned a worthy place in the history of Swiss archaeology, with the results often cited in various publications.